The potency of pinostrobin and pinocembrin as antiphotoaging agents: in silico study - Pradnyana, I Gusti Ngurah Agung; Putri, Ketut Yuantarisa Kartika; Susanti, Ni Made Pitri; Laksmiani, Ni Putu Linda (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2022)
Photoaging occurs when the skin ages due to ultraviolet light exposure. Phenolic compounds generally possess antioxidant activity, which helps prevent the formation of free radicals caused by sunlight exposure. This study explores the potential of pinostrobin and pinocembrin as antiphotoaging agents through molecular docking against matrix metalloproteinases (MMPs): MMP-1, MMP-3, and MMP-9. We utilized Hyperchem 8 to prepare and optimize the test compound and Chimera 1.11.1 for protein preparation. Validation and docking procedures were conducted using the AutoDockTools 1.5.6 application, with validation confirming that the method was valid with an RMSD value ≤ 3 Å. Both pinostrobin and pinocembrin exhibited an affinity for the target protein, although their affinity was slightly less than that of the native ligand and retinol. In conclusion, pinostrobin and pinocembrin demonstrate an affinity for MMP-1, MMP-3, and MMP-9, indicating their potential as anti-photoaging agents by obstructing the mechanisms of MMP-1, MMP-3, and MMP-9.